Bronchoalveolar lavage characteristics correlate with HLA tag SNPs in patients with Löfgren's syndrome and other sarcoidosis - Karakaya, B; Schimmelpennink, M C; Kocourkova, L; van der Vis, J J; Meek, B; Grutters, J C; Petrek, M; van Moorsel, C H M (Clinical and experimental immunology, 2019)
Genetic susceptibility for sarcoidosis and Löfgren's syndrome (LS) has been associated with prognosis. Human leukocyte antigen (HLA)-DRB1*03 is over-represented in LS, and is associated with a good prognosis, whereas HLA-DRB1*15-positive patients have a more chronic course of sarcoidosis. These HLA-DRB1 types can be easily tagged by single nucleotide polymorphisms (SNPs). Our aim was to evaluate the association between these tag SNPs and bronchoalveolar lavage (BAL) characteristics. In 29 patients, both complete HLA-DRB1* locus genotyping and SNP tagging was performed in parallel. HLA-DRB1 type was inferred from the presence of *03 tag rs2040410 allele A and referred to as *03. HLA-DRB1*15 was inferred from the presence of tag SNP rs3135388 allele A and referred to as *15. For BAL analysis, 122 patients with LS and 165 patients with non-LS sarcoidosis were included. BAL lymphocyte subsets were analyzed by flow cytometry. The presence of tag SNPs completely corresponded with HLA-DRB1*03/*15 genotypes in all 29 patients in whom both HLA-DRB1* genotyping and SNP tagging was performed. In all patients together, *03+ /*15- patients showed a higher CD4+ /CD8+ ratio than *03- /*15+ (P = 0·004) and *03- /*15- (P = 0·001). LS patients with *03+ /*15- had a lower BAL lymphocyte count compared to *03- /*15+ patients (P = 0·011). Non-LS sarcoidosis patients with *03+ /*15- patients showed a decreased CD103+ CD4+ /CD4+ ratio compared to *03- /*15+ patients (P = 0·045) and *03- /*15- patients (P = 0·018). We found that HLA-DRB1*03 and HLA-DRB1*15 can be approximated by genotyping of tag SNPs and corresponds with the degree of lymphocytosis and cell phenotypes in BAL in both LS and non-LS sarcoidosis patients.
Keywords: alely; jednonukleotidový polymorfismus; Alleles; bronchoalveolární laváž; T cells; MHC; Sarcoidosis, Pulmonary; plicní sarkoidóza; genotypizační techniky; Middle Aged; mužské pohlaví; Adult; HLA-DRB1 Chains; Genotyping Techniques; CD8-pozitivní T-lymfocyty; Humans; lung; HLA-DRB1 řetězec; lidé středního věku; CD4-pozitivní T-lymfocyty; dospělí; Bronchoalveolar Lavage; CD8-Positive T-Lymphocytes; CD4-Positive T-Lymphocytes; lidé; Male; Polymorphism, Single Nucleotide